The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12639-017-0968-5
|View full text |Cite
|
Sign up to set email alerts
|

Studies on prevalence and histomorphology of Sarcocystis species infecting cattle in Andhra Pradesh, India

Abstract: The present study was carried out to determine the prevalence of bovine sarcocystosis and identify the different species of cysts in cattle in different regions of Chittoor district, Andhra Pradesh. A total of 150 slaughtered cattle over a period of 1 year were examined both macroscopically and microscopically for the presence of infection. Out of 150 slaughtered cattle examined, macroscopic sarcocysts were observed in nine cattle and were exclusively found in oesophagus. Examination of tissue samples collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…Also, these results disagree with Abebe et al (2015) who recorded that 8.43% of 510 randomly selected slaughtered sheep and 8.5% of 420 randomly selected slaughtered goats were infected with C. ovis. The results of the current work revealed that the incidence of macroscopic Sarcocyst agree with Saeid et al (2015) who couldn't detect any macroscopic cysts in cattle and disagree with Mounika et al (2018) who observed macroscopic sarcocysts in nine cattle mainly in esophagus. The incidence in sheep disagrees with Aysen et al (2007) who found macrocysts of Sarcocyst ovifelis in (24.5%) of sheep mainly in esophagus.…”
Section: Discussionsupporting
confidence: 67%
“…Also, these results disagree with Abebe et al (2015) who recorded that 8.43% of 510 randomly selected slaughtered sheep and 8.5% of 420 randomly selected slaughtered goats were infected with C. ovis. The results of the current work revealed that the incidence of macroscopic Sarcocyst agree with Saeid et al (2015) who couldn't detect any macroscopic cysts in cattle and disagree with Mounika et al (2018) who observed macroscopic sarcocysts in nine cattle mainly in esophagus. The incidence in sheep disagrees with Aysen et al (2007) who found macrocysts of Sarcocyst ovifelis in (24.5%) of sheep mainly in esophagus.…”
Section: Discussionsupporting
confidence: 67%
“…A prevalence of 100% was reported by Shekarforoush et al [29]. The prevalence rates of 95.5%, 91.33%, and 88.2% were reported by Mavi et al [30], Mounika et al [31], and Shahraki et al [32], respectively.…”
Section: Discussionmentioning
confidence: 90%
“…A dificuldade de diagnosticar e evidenciar lesões macroscópicas de cistos musculares na inspeção de carnes em abatedouros faz com que este músculo venha a ser comercializado, o que não ocorre, por exemplo, com lesões provocadas por cisticercos de Taenia saginata, que são facilmente visualizadas e diagnosticadas na musculatura, uma vez que ambos parasitos têm predileção por músculos com bom suprimento sanguíneo. As observações de macrocistos de Sarcocystis na musculatura (cardíaca ou diafragma) normalmente são causadas por S. hirsuta e S. hominis, porém S. cruzi é a espécie mais frequente na musculatura de bovinos, no Brasil e no mundo (Ghisleni et al, 2006;Mounika et al, 2018;Nourani et al, 2010;Nourollahi-Fard et al, 2015). Por serem intracelulares os sarcocistos de Sarcocystis estão protegidos das defesas imunes do hospedeiro, por esta razão na maioria dos casos não ocorre uma resposta inflamatória e o achado do protozoário em lâminas de músculo estriado é comum na rotina histopatológica (Tessele et al, 2013).…”
Section: Resultsunclassified